2005
DOI: 10.1590/s0074-02762005000700020
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular polyamine pools, oligopeptide-binding protein A expression, and resistance to aminoglycosides in Escherichia coli

Abstract: The role of intracellular free polyamine (putrescine and spermidine)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
(26 reference statements)
0
8
0
1
Order By: Relevance
“…OppA is an oligopeptide ABC transporter substrate‐binding protein that constitutes an oligopeptide permease transport system that is responsible for the transport of oligopeptides into cells (Wium, Botes, & Bellstedt, ). Aminoglycoside antibiotics were transferred into cells through the oligopeptide permease transport system, and the reduced expression of OppA was associated with aminoglycoside resistance (Acosta, Ferreira, Ferreira, & Costa, ). It has been reported that the oligopeptide transport system was important for the uptake of aminoglycoside antibiotics since a decrease in OppA was observed in approximately 40% of spontaneous aminoglycoside‐resistant mutant (Kashiwagi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…OppA is an oligopeptide ABC transporter substrate‐binding protein that constitutes an oligopeptide permease transport system that is responsible for the transport of oligopeptides into cells (Wium, Botes, & Bellstedt, ). Aminoglycoside antibiotics were transferred into cells through the oligopeptide permease transport system, and the reduced expression of OppA was associated with aminoglycoside resistance (Acosta, Ferreira, Ferreira, & Costa, ). It has been reported that the oligopeptide transport system was important for the uptake of aminoglycoside antibiotics since a decrease in OppA was observed in approximately 40% of spontaneous aminoglycoside‐resistant mutant (Kashiwagi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular polyamine pools affect, at the posttranscriptional level, OppA expression and the action of aminoglycosides in E. coli K12 (Goldemberg & Algranati, 1981; Acosta et al , 2005). Indeed, addition of polyamines to the growth medium enhances the sensitivity of E. coli K12 strains to aminoglycosides, while low intracellular polyamine pools may reduce OppA expression and aminoglycoside sensitivity (Kashiwagi et al , 1998; Acosta et al , 2005). Although the role of polyamines in OppA expression has been clearly established (Igarashi et al , 1997), further studies are required to elucidate the impact of polyamines on the sensitivity to aminoglycosides.…”
Section: Discussionmentioning
confidence: 99%
“…Para tal, o modo de avaliação considerado padrão-ouro do papel fisiológico dos sistemas de transporte de nutrientes baseia-se no emprego de moléculas radioativamente marcadas, quando disponíveis, no qual é possível mensurar a incorporação destas, bem como avaliar as características bioquímicas do sistema de transporte (KRASTEL et al, 2010;RAKSAJIT et al, 2006). (ACOSTA et al, 2005;AMES et al, 1973;NAIDER et al, 1975;NAKAMATSU et al, 2007;RUDNER et al, 1991 Além da captação de oligopeptídeos ser um fator importante para a sobrevivência, seu papel fisiológico pode ser estendido, como observado em E. coli e S. Typhimurium, nas quais esse sistema é responsável pela reciclagem de até 50% da peptideoglicana da parede celular bacteriana (GOODELL et al, 1987;PARK et al, 1998). Em diversas bactérias gram-positivas, como Bacillus subtilis e Streptococcus pneumoniae, a capacidade de transformação se deve a respostas a comunicações intercelulares dependentes de peptídeos e que só ocorrem na presença de um sistema de captação de oligopeptídeos funcional, incluindo no mínimo um ortólogo de OppA (ALLOING et al, 1998;PEARCE et al, 1994;RUDNER et al, 1991).…”
Section: Figura 1-sistema De Transporte Abcunclassified